A critical discourse analysis of news on forest resources in Turkish newspapers - Narin, Tuncay; Durusoy, İdris; Gürses, Fatma (Frontiers in Forests and Global Change, 2025)
This study investigates how Turkish newspapers frame forest-related issues through a critical discourse analysis of articles published in Cumhuriyet, Posta, and Sabah between 2010 and 2021. Utilizing Teun A. van Dijk’s critical discourse analysis approach, the articles were categorized into four main themes: deforestation, forest fires, afforestation, and other forestry issues. Selected articles from each newspaper on these themes were analyzed. Findings reveal significant editorial differences; Cumhuriyet adopted a critical stance, highlighting governmental inadequacies, while Sabah employed supportive narratives portraying government efforts as effective. Posta aligned somewhat with the government by avoiding criticism and emphasizing neutral causes like global warming. The analysis underscores discrepancies in thematic structures, background context, and source selection, influenced by each newspaper’s ideological alignment. Additionally, the crisis-oriented discourse prevalent across themes accentuated forest fires and their consequences. The study concludes that ideological orientations significantly shape media portrayals of forestry issues, influencing public perception and policy dialogue. Enhancing environmental journalism and fostering collaboration between media and forestry experts are recommended to improve public understanding of forest management challenges.